2020
DOI: 10.1007/s42832-020-0050-6
|View full text |Cite
|
Sign up to set email alerts
|

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils

Abstract: Dissimilarity nitrate reduction to ammonium (DNRA) is of significance in agriculture ecosystems as the process is beneficial to N retention in soils. However, how fertilization regimes influence DNRA rates and functional microbes in agriculture was rarely estimated. In the present study, a 2-year pot experiment was conducted in two contrasting paddy soils to evaluate the effects of straw and nitrogen addition on DNRA process and the related functional microbes, using stable isotope tracer and molecular ecology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
(90 reference statements)
1
11
1
Order By: Relevance
“…Soil pH is the second most important factor controlling DNRA as it is stimulated at higher soil pH. This result is consistent with previous results of Corrêa and Germon, Stevens et al, and Bai et al., who found that higher DNRA is often recorded in alkaline environments. Similarly, Zhang et al recorded 98% conversion of NO 3 – to NH 4 + by the DNRA in alkaline soil.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Soil pH is the second most important factor controlling DNRA as it is stimulated at higher soil pH. This result is consistent with previous results of Corrêa and Germon, Stevens et al, and Bai et al., who found that higher DNRA is often recorded in alkaline environments. Similarly, Zhang et al recorded 98% conversion of NO 3 – to NH 4 + by the DNRA in alkaline soil.…”
Section: Discussionsupporting
confidence: 92%
“…Soil pH regulates DNRA through its effect on the abundances of nrfA, nitrite reductase-encoding gene related to DNRA, which reaches its optimum activity at pH > 7.5 . Higher DNRA rates are linked with higher nrfA gene levels. ,, Recently, Bai et al found that DNRA rates and the transcription activity and abundance of nrfA were significantly lower in acidic soils than that in alkaline soils. Moreover, soil microbial activity enhanced with raising soil pH from 3.0 to 7.7, thus stimulating DNRA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations